Association between gestational age and persistent pulmonary hypertension of the newborn (PPHN) severity in preterm babies at Sidoarjo Regional Hospital - Aisyah Faadhilah; M. Perdana Airlangga; Nurma Yuliyanasari; Gina Noor Djalilah (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2021)
AbstractPersistent pulmonary hypertension of the newborn (PPHN) is a condition that occurs due to increased resistance to blood vessels in the lungs that occur persistently after the baby is born. This can be attributed to congenital heart disease such as right-to-left shunts through foramen ovale (PFO) or patent ductus arteriosus (PDA) due to an error transition fetal blood circulation to the neonate. Although PPHN is always associated with births in post-term babies, PPHN cases are often found in preterm babies. Chances of babies born with PPHN are quite large, at 1.9% per 1000 live births. PPHN can be fatal, causing mortality rates ranging from 4 to 33%. The incidence of preterm births in Indonesia is estimated at 7-14%, around 459,200 - 900,000 babies per year. This study aimed to prove the relationship between premature babies and persistent pulmonary hypertension of the newborn (pphn) in Sidoarjo  Regional Hospital and to know the characteristics and analyze these variables.  This research used crossed sectional studied design; the population was all preterm babies in the NICU at Sidoarjo  regional hospital. All samples are from medical records in January-December 2018. There is a significant difference between preterm babies and PPHN (p < 0.05); besides, the results from Spearman's correlation analysis obtained a correlation coefficient (ρ) = 0.485. In the cross-tabulation analysis, the result of the proportion with the highest correlation was Late Preterm babies with severe PPHN of 46.7%. It can be concluded that there is a relationship between premature babies and PPHN in Sidoarjo  regional hospital..Keywords                      : Persistent pulmonary hypertension of the newborn, PPHN, Preterm BabiesCorrespondence            : aisyahhelmadevithalib@gmail.com